Can u please restate the question

Thanks

**Answer:**

The answer to your question is **x = 0** and **x = 1**

**Step-by-step explanation:**

**Equation **

1)

Expand

2) x² + x + x² - x - 2x + 2 = -1(x - 2)(x + 1)

Simplify

3) 2x² -2x + 2 = -1(x² + x - 2x - 2)

4) 2x² - 2x + 2 = -x² + x + 2

Equal to zero

5) 2x² - 2x + 2 + x² - x - 2 = 0

6) 3x² - 3x = 0

Factor

7) 3x(x - 1) = 0

8) 3x₁ = 0 x₂ - 1 = 0

9) x₁ = 0/3 x₂ = 1

**10) x₁ = 0 x₂ = 1**

V = πr²h

**h = V / πr²**

Hope it helped. Let me know, if have some doubts

The total cost is $100.70